Combined effects of temperature-related variables on trhe viability of probiotic micro-organisma in yogurt - Mortazavian, A M (2006)
Combined effects of temperature-related variables including heat treatment, incubation temperature and refrigerated storage temperature on the viability of probiotic micro-organisms in ABY-type probiotic yogurt (Lactobacillus acidophilus, bifidobacteria and yogurt bacteria) were studied. Three heat treatments (85°C for 30 min, 95°C for 5 min and 95°C for 15 min), three incubation temperatures (37°C, 40°C and 44°C) and three refrigerated storage temperatures (2°C, 5°C and 8°C) were selected. Interactive effects of heat treatment and incubation temperature on the viability of probiotics were considered at the end of fermentation. Then, the highest viability of probiotics was investigated as a function of refrigerated storage temperature during refrigerated storage for 20 days. The viability change of the probiotic micro-organisms was analysed at five-day intervals throughout the refrigerated storage period. The final objective was to find the best combination of (heat treatment/incubation temperature/refrigerated storage temperature) for the viabilities of the probiotics. At the end of fermentation, the maximum viability of probiotics (for both L. acidophilus and bifidobacteria) was observed when the yogurt milk was heated at 95°C for 15 min and incubated at 37°C. Storage at 2°C for 20 days resulted in the highest viability of L. acidophilus, while for bifidobacteria the highest viability was obtained when yogurt was stored at 8°C.